Liver Fibrosis Indices for Identifying Patients at Low Risk of Developing Hepatocellular Carcinoma after Eradication of HCV. Issue 3 (April 2017) - Toyoda, Hidenori; Tada, Toshifumi; Tachi, Yoshihiko; Hirai, Takanori; Yasuda, Satoshi; Honda, Takashi; Hayashi, Kazuhiko; Ishigami, Masatoshi; Goto, Hidemi; Kumada, Takashi
Background: Hepatocellular carcinoma (HCC) in patients with chronic hepatitis C can develop after sustained virological response (SVR) to antiviral therapy for HCV, that is, the eradication of HCV, and effective surveillance systems for HCC should be established for this population. We retrospectively evaluated the utility of three laboratory liver fibrosis indices (aspartate aminotransferase-platelet ratio index [APRI], FIB-4 index and Forns index) for identifying patients at low risk of HCC development after SVR, for whom the termination of surveillance for HCC can be considered. Methods: APRI, FIB-4 index and Forns index scores were calculated based on laboratory data prior to anti-HCV therapy and at 24 weeks after the end of anti-HCV therapy (SVR24) in 522 patients with SVR who continued surveillance for HCC after SVR. The associations between HCC development and laboratory indices at both points were analysed. Results: Twenty-one patients developed HCC after SVR during 2.3–24.4 years follow-up. Whereas HCC developed even in patients with low APRI or FIB-4 index scores, no patients with low Forns index scores developed HCC after SVR. These results were confirmed in a separate cohort of 309 patients who achieved SVR (HCC developed in 17 patients during 1.7–21.6 years follow-up). Conclusions: Forns index, especially assessed prior to anti-HCV therapy, was a useful laboratory liver fibrosis index for identifying patients at low likelihood of HCC after SVR. This index may be used as one of indicators to consider the termination of surveillance for HCC after the eradication of HCV.